Heavy metal background levels and pollution temporal trend assessment within the marine sediments facing a brownfield area (Gulf of Pozzuoli, Southern Italy) - Giovanna Armiento; Mattia Barsanti; Raffaela Caprioli; Salvatore Chiavarini; Fabio Conte; Cinzia Crovato; Maurizio De Cassan; Ivana Delbono; Maria R. Montereali; Elisa Nardi; Luisa Parrella; Massimo Pezza; et al. (Environmental Monitoring and Assessment, 2022)
In this study, site-specific natural background levels (NBLs) were determined for 18 elements (Al, As, Be, Cd, Co, Cu, Cr, Fe, Hg, K, Mn, Mo, Ni, Pb, Tl, U, V, and Zn) in two sediment cores collected offshore the Bagnoli-Coroglio brownfield site (Gulf of Pozzuoli, southern Italy) to accurately assess the degree of contamination and the historical trends in Heavy Metals (HMs) enrichment. This objective was pursued taking in account the high temporal and spatial variability of the geochemical properties of the area due to the local geothermal activity. Moreover, the temporal variation of Polycyclic Aromatic Hydrocarbons (PAHs) was investigated. 226 Ra was used as an extraordinary marker to confirm 210 Pb dating. It especially allowed defining the geochronological framework of the sediment core closer the brownfield up to around 1500, providing compelling support to correlate the investigated elements’ occurrences with natural geogenic dynamic. Sediment samples were accurately dated and analyzed for chemical and particle size composition. The contamination factor (Cf) and the pollution load index (PLI) showed very high enrichment of Cd, Cu, Hg, Pb, and Zn. The contamination profiles of HMs and PAHs follow the same pattern in both sediment cores, increasing from deep to upper layers. The highest contamination levels for HMs and PAHs were observed between 10 and 30 cm, corresponding to the periods of most intense industrial activity. Decreasing trends of pollutants were observed in the surface layers (0–10 cm), probably affected by a natural attenuation process due to the cessation of industrial activities.